(untitled) (CIPEEX, 2022)
ACCORDING TO RESEARCHES CONDUCTED ON 2015, MORE THAN 170 THOUSAND ANIMALS ARE UNDER CAREOF AROUND 370 NON-GOVERNMENTAL ORGANIZATIONS (NGOS) WAITING FOR ADOPTION ON BRAZIL, INADDITION TO MORE THAN 30 MILLION STRAY CATS AND DOGS. MAKING PET NEGLECT AND ABANDONMENTSOMETHING NOT JUST CRUEL, BUT ALSO A PROBLEM OF SANITARY NATURE. TO FACE THIS ISSUE ON A LOCALSCOPE, BUDDYRESC IS BORN AS A MOBILE APP WITH THE PURPOSE OF FACILITATING PET ADOPTION ANDREDUCING THE OCCURRENCE OF ANIMAL ABANDONMENT, MAKING THIS PROCESS EASIER, USER FRIENDLY ANDMORE HUMANIZED. THE PROJECT AIMS TO ALLOW VERIFIED PEOPLE AND ORGANIZATIONS TO REGISTER ANIMALSAND CAMPAIGNS SO USERS CAN VIEW THEM, CONTACT CURRENT TUTORS AND GIVE A NEW HOME FOR THOSEIN NEED. THIS WAY, IF SOMEONE IS FOSTERING OR TUTORING AND COULD NOT TAKE CARE OF A PET ANYMORE,THEY WOULD REGISTER THE ANIMAL ON THE SYSTEM INSTEAD OF IMMEDIATELY ABANDONING IT, GIVING THEMANOTHER CHANCE OF STAYING OF THE STREETS.